Antigenic characterization and analysis of the human immune response to outer membrane protein E of Branhamella catarrhalis. - Bhushan, R (1997)
Outer membrane protein E (OMP E) is a 50-kDa major OMP of Branhamella catarrhalis. Polyclonal antisera and four monoclonal antibodies (MAbs) to OMP E were generated to study its antigenic structure. All antibodies recognized epitopes in all 19 B. catarrhalis strains tested by immunoblot assays. By flow cytometry, it was determined that MAbs 1B3 and 9G10d recognized epitopes which are expressed on the surface of the intact bacterium, while MAbs IC11 and 7C10 recognized epitopes which were buried within the outer membrane. A competitive enzyme-linked immunosorbent assay showed that MAbs 1B3 and 9G10d recognize the same or closely related epitopes. Proteinase K treatment of whole bacterial cells revealed that MAbs 1B3 and 9G10d recognize a surface-exposed epitope located in the 17-kDa region towards the amino terminus of OMP E. The human serum and mucosal antibody responses to OMP E in adults with chronic bronchitis were studied. A majority of these patients had immunoglobulin A to OMP E in sputum supernatants. None of ten adults who experienced lower respiratory tract infections due to B. catarrhalis demonstrated a clear-cut rise in antibody titer to OMP E in serum or sputum supernatant. This study has demonstrated that OMP E has at least one surface-exposed epitope which is highly conserved among strains of B. catarrhalis and which is located in the amino-terminal 184 amino acids of the molecule.